THE IMPACT OF ELECTION CAMPAIGN ON ELECTION RESULTS IN THE REPUBLIC OF SERBIA - Jovanović, Nevena D. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Election campaigns, as essential political activities, receive great attention because of their potential to significantly influence voters, and therefore the final outcome of the electoral process. For precisely this reason, the election campaigns in the 21th century are carefully planned and implemented. Taking into account all the elements and structure of the election campaign, special consideration should be given to media which are extremely powerful in terms of placing political messages and shaping public attitudes and opinions, particularly those of abstaining voters, first-time voters or voters not identifying with any party. In this respect, through a review of components of the election campaign, the paper aims to point to its importance and the impact it has on election results, with particular reference to the election campaign for presidential elections in the Republic of Serbia in 2017.